Тактичні особливості огляду місця події під час розслідування захоплення представника влади або працівника правоохоронного органу як заручника - Прокопенко, О.Ю.; Prokopenko, O.Yu. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 4 (103). - С. 255-262, 2023)
У статті приділено увагу тактичним особливостям проведення огляду місця події під час розслідування захоплення представника влади або працівника правоохоронного органу як заручника за нормами чинного Кримінального процесуального кодексу України. Описано визначення поняття «огляд місця події» під час проведення досудового розслідування за ст. 349 Кримінального кодексу України. Визначено орієнтовний перелік місць, де виникає необхідність у проведенні такої слідчої (розшукової) дії, як огляд. Приділено увагу визначенню суб’єктного складу учасників, задіяних у проведенні слідчої (розшукової) дії. Також розглянуто питання техніко-криміналістичного забезпечення проведення огляду місця події.

The criminal offence of taking a government official or a law enforcement officer hostage under Article 349 of the Criminal Code of Ukraine is becoming increasingly relevant in today’s realities. However, in the course of the study of scientific findings, the absence of methodological recommendations for investigating this crime has been established, which negatively affects the state of combating crime. In particular, the investigation methodology includes recommendations on the specifics of certain investigative (detective) actions, the primary of which is the inspection of the scene. Thus, there is a need to conduct research on the above issue. The purpose of the study is to determine the tactical features of conducting an inspection of the scene of a hostage-taking of a government official or law enforcement officer. To achieve this research goal, the analysis of scientific literature, investigative and judicial practice has been carried out. The article outlines some peculiarities of the tactics of examining the scene of an incident, and identifies the necessary material and technical and forensic support for such an investigative (detective) action. The article also provides examples of possible evidence to be considered at the scene of an event. Based on the results of the study, some tactical techniques for inspecting the scene of a seizure of a government official or a law enforcement officer have been identified, and the inspection has been classified depending on the location: 1) the place of seizure; 2) the place of movement of the seized person; 3) the place of detention of the hostage; 4) the place of detention of the perpetrator. For each place of inspection, the peculiarities and the relevant algorithm of actions by the pre-trial investigation authorities have been identified. It has been established that the purpose of conducting a crime scene investigation of the criminal offences under study is to: establish the location and release of a hostage; establish the location and detention of suspects; identify and seize tools, means of committing a crime and other things relevant to criminal proceedings.

В статье уделено внимание тактическим особенностям проведения осмотра места происшествия при расследовании захвата представителя власти или работника правоохранительного органа как заложника по нормам действующего Уголовного процессуального кодекса Украины. Описано определение понятия «осмотр места происшествия» при проведении досудебного расследования по ст. 349 Уголовного кодекса. Определен ориентировочный перечень мест, где возникает необходимость в проведении такого следственного (розыскного) действия, как обзор. Уделено внимание определению субъектного состава участников, задействованных в проведении следственного (розыскного) действия. Также рассмотрены вопросы технико-криминалистического обеспечения проведения осмотра места происшествия.
Tactical features of the scene inspection in the investigation of the taking of a government official or law enforcement officer as a hostage
Keywords: кримінальне провадження; огляд місця події; захоплення; заручники; працівник правоохоронного органу; представник влади; criminal proceedings; inspection of the scene; seizure; hostages; law enforcement officer; government official; уголовное производство; осмотр места происшествия; захват; заложники; работник правоохранительного органа; представитель власти